Heterogeneous distribution of histone methylation in mature human sperm - la Spina, Florenza Antonella (2014)
Purpose To analyze the presence of various histone modifications in ejaculated human spermatozoa Methods In this prospective study, seminal ejaculates from 39 normozoospermic individuals were evaluated for semen analysis and the presence of histone modifications in isolated nuclei. Results We observed heterogeneous presence of histone methylation in normal mature human sperm. We observed that 12 to 30 % of the nuclei of normal sperm contain a heterogeneous distribution of the marks H3K4Me1, H3K9Me2, H3K4Me3, H3K79Me2, and H3K36Me3. Moreover, the presence of these marks is higher in the poor motile fraction of the ejaculate, which is associated with poor morphology and functional quality. In contrast, we did not observe histone acetylation (H3K4Ac and H4K5Ac) in normal or abnormal mature human sperm Conclusions Defects in the process of spermatogenesis may alter the correct epigenetic programing in mature sperm. Further studies are required to evaluate the impact of these findings in human infertility